Using Electrical Charge Method to Understand Biochemical Reactions - Yuen, Pong Kau; Lau, Cheng Man Diana; Yuen, Kuok In Gabriel (Universitas Tidar, 2024)
Redox reactions are important in many physiological processes. Oxidation numbers are commonly used for balancing redox reactions and understanding metabolic reactions. When oxidation number cannot be assigned, it is difficult or sometimes even impossible to understand the biochemical redox reactions. This article applies the electrical charge method, which can balance redox reactions when the oxidation number is unknown. It uses H+, O, H2O, and electric charge as balancing devices. This method allows the net-charge to be quantified, redox terms to be defined, and metabolic redox reactions to be classified and understood. The net-charge is also a new electron-counting parameter for understanding biochemical redox reactions.